2017
DOI: 10.1016/j.jhazmat.2016.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of polycyclic aromatic hydrocarbons (PAHs) in Arabidopsis thaliana involves a putative flavonol synthase

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are environmental contaminants with cytotoxic, teratogenic and carcinogenic properties. Bioremediation studies with bacteria have led to the identification of dioxygenases (DOXs) in the first step to degrade these recalcitrant compounds. In this study, we characterized the role of the Arabidopsis thaliana AT5G05600, a putative DOX of the flavonol synthase family, in the transformation of PAHs. Phenotypic analysis of loss-of-function mutant lines showed that these plant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…In the KEGG analysis, the MtFLSs were downregulated in mtbzr1-1 . Their homolog in A. thaliana , At5g05600 , functions as a flavonol synthase and a 2-oxoglutarate/Fe (II)-dependent oxygenase that hydroxylates jasmonic acid (JA) [23]. Consist with this, we found that genes involved in linoleic acid metabolism (ko00591) were enriched with DEGs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the KEGG analysis, the MtFLSs were downregulated in mtbzr1-1 . Their homolog in A. thaliana , At5g05600 , functions as a flavonol synthase and a 2-oxoglutarate/Fe (II)-dependent oxygenase that hydroxylates jasmonic acid (JA) [23]. Consist with this, we found that genes involved in linoleic acid metabolism (ko00591) were enriched with DEGs.…”
Section: Discussionmentioning
confidence: 93%
“…Consist with this, we found that genes involved in linoleic acid metabolism (ko00591) were enriched with DEGs. Linoleic acids are precursors for JA, which inhibits the calcium spiking induced by Nod factors [23,24]. As an important transcription factor in BR signaling, MtBZR1 might function in hormone cross-talk in nodule development.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated changes in expression levels of NAP2 and GSTU25 in response to oil contamination may be related to their sequential role in the PAHs detoxification process. As the first step of detoxification, members of the cytochrome P450 family catalyze the oxidation of potentially toxic compounds, which are subsequently conjugated to a hydrophilic molecule, such as glucose, glutathione or glucuronide [ 50 , 51 ]. This conjugation step makes the potentially toxic compounds more hydrophilic and prevents the newly formed compounds from crossing membranes by diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial association relies on the fact that bacteria increase the bioavailability and degradation of organic pollutants, in turn, plants provide residency and food to the bacteria (Muratova et al, 2003;Weyens et al, 2009).Despite the fact that rhizoremediation happens naturally, but through deliberate manipulation (inoculating the soil with contaminant degrading and/or PGP bacteria) in rhizosphere it can be enhanced (Hernández-Vega et al, 2017;Vergani et al, 2017).…”
Section: Rhizoremediation: Use Of Rhizobacteria To Enhance Hydrocarbomentioning
confidence: 99%